The Relationship between Service Response Time and Waiting Time for Transfer of IGD Patients to Inpatients with Patient Satisfaction - Akbar; Andi Lis Arming Gandini; Diah Setiani (PT FORMOSA CENDEKIA GLOBAL, 2023)
The front line hospital services are the Emergency Room where the services provided are immediate, fast, precise and accurate. The services provided will affect patient satisfaction. One that is closely related to patient satisfaction in the emergency room is service response time and waiting time for patient transfer to inpatient care. This study aims to determine the relationship between service response time and patient transfer time to inpatient care with patient satisfaction at RSUD dr. Abdul Rivai in 2022. The design of this study was an analytic observational Cross Sectional design with a quantitative non-experimental approach to research methods with relationship analysis using the chi-square test. Based on the results of the bivariate test, it was found that P-Value = 0.016 on the relationship between service response time and patient satisfaction, and P-Value = 0.002 on the relationship between transfer time and patient satisfaction. There is a significant relationship between service response time and waiting time for patient transfer to the inpatient room with patient satisfaction.